'Is this knowledge mine and nobody else's? I don't feel that.' Patient views about consent, confidentiality and information-sharing in genetic medicine. Issue 3 (7th January 2016) - Dheensa, Sandi; Fenwick, Angela; Lucassen, Anneke
Abstract : In genetic medicine, a patient's diagnosis can mean their family members are also at risk, raising a question about how consent and confidentiality should function in clinical genetics. This question is particularly pressing when it is unclear whether a patient has shared information. Conventionally, healthcare professionals view confidentiality at an individual level and 'disclosure without consent' as the exception, not the rule. The relational joint account model, by contrast, conceptualises genetic information as confidential at the familial level and encourages professionals to take disclosure as the default position. In this study, we interviewed 33 patients about consent and confidentiality and analysed data thematically. Our first theme showed that although participants thought of certain aspects of genetic conditions—for example, the way they affect day-to-day health—as somewhat personal, they perceived genetic information—for example, the mutation in isolation—as familial. Most thought these elements were separable and thought family members had a right to know the latter, identifying a broad range of harms that would justify disclosure. Our second theme illustrated that participants nonetheless had some concerns about what, if any, implications there would be of professionals treating such information as familial and they emphasised the importance of being informed about the way their information would be shared. Based on these results, we recommend that professionals take disclosure as the default position, but make clear that they will treat genetic information as familial during initial consultations and address any concerns therein.